Aspecte teoretice privind proprietăţile colorimetrice ale produselor peliculogene - Alina Dima; Vasilica Vasile; Mihaela Ion (Urbanism. Arhitectura. Constructii, 2012)
The paper presents, in the first part, general notions about the nature of color, such as: elements of color theory, light sources and illuminants, observer standard, necessary for understanding photochemical mechanisms occurring in the macromolecular matrix and pigments, major components of the complex chemical system represented by the filmforming product. In the second part, are highlighted physical phenomena that may arise from interaction of light with colored surfaces of the coating products.